Benturan Paradigma: Respons terhadap Penggeseran Paradigma Islam: Clash of Paradigms: A Response to the Shifting of Islamic Paradigms - Manilet, M. Jamil; Al Kindi, Farhan Afif (Center of Islamic and Occidental Studies, 2024)
The clash between paradigms, in this case the Islamic and Western paradigms, is inevitable. This cannot be separated from the globalization that has swept the world. Religious issues from various regions around the world are easily accessible to anyone, anywhere, and anytime. The influx of these issues shapes the patterns and attitudes of Muslims, both in dealing with external and internal problems. The problem is that Muslims are then forced to submit to the Western paradigm. Since the late 19th century, Western penetration of the Islamic world has at least forced some Muslim countries to adopt Western laws. In addition, Islamic academics and intellectuals have lately been moving towards a rationalism-nihilism paradigm that tends to be oriented towards Western orientalist thought and philosophy. As a result, the Islamic paradigm adopted as a framework for Muslims' thinking has shifted and been replaced with a secular-liberal Western paradigm. Therefore, Islamic law is considered to be in conflict with human rights and the way of life of modern society. Departing from that, this paper is important as a response as well as an analysis and offer that the Islamic paradigm is different from the Western paradigm, so the products produced are also different. The Islamic paradigm is not just a view of the human mind towards the physical world or human involvement in it from a historical, social, political, and cultural perspective, but includes aspects of the world and the hereafter.